Pengembangan Sistem Skrining Kesehatan Berbasis Web dengan Metode Extreme Programming di STT-NF - Apriyana, Andre; Nasrul, Nasrul (LPPM STT Terpadu Nurul Fikri, 2025)
Nurul Fikri Integrated Technology College (STT-NF) has encountered challenges in managing health screening data, which is currently handled manually using Microsoft Excel. This approach lacks efficiency, security, and accessibility. This study aims to implement the Extreme Programming (XP) methodology in developing a web-based health screening information system using the Laravel Framework. The system is designed to provide easy access, enhanced security, and a well-structured data management process without requiring additional installations on user devices. The development process follows the iterative and adaptive stages of the Extreme Programming methodology to better align with user needs. The system features key functionalities, including physical examinations and screenings for uric acid, cholesterol, blood sugar, and blood pressure. Testing was conducted using Black Box Testing and User Acceptance Testing (UAT). Black Box Testing showed a 100% success rate across 40 scenarios, while UAT, involving one staff member and one student, demonstrated an average success rate of 100%. The results indicate that the developed system not only improves the efficiency and accuracy of health screening data management but is also well-received by end Users. Supported by the Laravel Framework, this web-based system successfully meets the health screening service requirements at STT-NF.